Performance analysis of the clustering-based multihop wireless energy harvesting sensor networks over symmetric and asymmetric fading channels - Vikash Singh; Hideki Ochiai (International Journal of Distributed Sensor Networks)
In this work, we propose a clustering-based multihop relaying with the partial relay selection scheme for an energy harvesting relaying network and analyze the performance in the framework of the decode-and-forward relaying and adaptive power splitting protocol over symmetric and asymmetric fading channel models. In particular, we analyze the system performance in terms of the outage probability, effective transmission rate, and throughput. Through extensive numerical analysis, we show that the proposed scheme can substantially outperform the conventional multihop relaying without clustering as well as direct transmission, which suggests that the proposed scheme can be used to extend the network coverage without any extra energy from the network. We also demonstrate that the proposed scheme can compensate for the performance loss due to poor radio frequency to DC conversion efficiency as well as path loss by exploiting the gain associated with multihop relaying as well as the diversity gain achieved through the partial relay selection scheme. Moreover, we investigate the relationship between the total number of relay nodes in the network and the number of hops and show that there is an optimal number of hops that can maximize the throughput for a given transmission power of the source. The effect of the asymmetric channels in our clustering-based multihop relaying is also investigated and it is revealed that the existence of Rician fading will help improve the throughput at the destination side, rather than the source side, as opposed to the conventional multihop relaying scenarios without clustering.